Chronic tophaceous gout treated mistakenly as rheumatoid arthritis for one year - Ulusoy, Hasan; Akgol, Gurkan; Gulkesen, Arif; Kamanli, Ayhan (TIP ARASTIRMALARI DERNEGI, 2012)
Gout is a common disorder characterized by hyperuricemia and the deposition of monosodium urate crystals in various tissues. Clinical manifestations of gout include attacks of acute inflammatory arthritis, a chronic destructive arthropathy known as chronic tophaceous gout, and non-articular accumulation of monosodium urate crystals crystals suchs as tophi and kidney stones. Acute gouty arthritis usually begins with one joint in the lower limbs, such as first metatarsophalangeal joint, midtarsi, ankles and knees. Subsequent attacks frequently last longer than does the first attack, affect several joints, and are prone to spread to the upper limbs, especially to small joints of the hands. Although acute gouty arthritis is familiar for most physicians chronic gouty arthritis which affects small joints of the hands can be difficult to distinguish from other common interphalangeal arthropathies such as rheumatoid arthritis, psoriatic arthritis and erosive osteoarthritis. Because of very similar presentations, an awareness of the differential diagnosis, as well as a combination of clinical, radiographic, and laboratory findings is necessary to differentiate these diseases. Here we describe a case of chronic tophaceous gout who had been treated mistakenly as rheumatoid arthritis for one year.
Bir yıl romatoid artrit olarak takip edilen kronik tofüsllü gut
Keywords: Chronic tophaceous gout; Gout; Gouty arthritis; Interphalangeal arthropathies